Kerja Sama Kawasan Asia Tenggara Menghadapi Perdagangan Orang dan Penipuan Online - Muhammad Syaroni Rofii (Badan Strategi Kebijakan Hukum, 2026)
This study aims to analyze the phenomenon behind the high number of cases of Human Trafficking (TPPO) in Indonesia, how criminal networks operate across the ASEAN region exploiting legal and regulatory loopholes to commit online fraud, human trafficking, extortion, and torture, and how the Indonesian government's strategy responds to existing cases within the legal framework and cooperation of the ASEAN region. This research is a qualitative case study research using primary data in the form of in-depth interviews with the Indonesian Ministry of Foreign Affairs, the Indonesian National Police, especially the Police Attachés in Bangkok, Manila, and Kuala Lumpur, as well as migrant activists. Researchers also conducted observations at points that have been the departure and arrival points for victims of TPPO. The results of this study confirm that the problem of TPPO arises as a result of legal disharmony at the regional level and compliance with conventions such as ACTIP in the region is based on voluntary compliance. As a result, law enforcement agencies face obstacles in coordinating agreements because they do not yet have an integrated criminal data system, requiring bilateral cooperation and joint operations that are ad hoc and limited in nature. In conclusion, the problem of human trafficking is very complex and is not only a problem for the central and regional governments in Indonesia but also a problem for the ASEAN region. Therefore, in order to achieve regional resilience in facing this situation, joint efforts are needed in the form of continuous cross-border cooperation within the ASEAN framework.